Significance of Time Until PSA Recurrence After Radical Prostatectomy Without Neo- or Adjuvant Treatment to Clinical Progression and Cancer-Related Death in High-Risk Prostate Cancer Patients - Venclovas, Zilvinas; Jievaltas, Mindaugas; Milonas, Daimantas (Frontiers in Oncology, 2019)
The aim of our study was to evaluate the impact of time until biochemical recurrence (BCR) after radical prostatectomy (RP) without neo- or adjuvant treatment on clinical progression (CP) and cancer related death (CRD) in high-risk prostate cancer (HRPCa) patients. 433 men with clinically HRPCa treated between 2001 and 2017 were identified. HRPCa was defined as clinical stage T2c and/or biopsy Gleason score (GS) 8 and/or preoperative prostate specific antigen (PSA) value >20ng/ml. Exclusion criteria were neo- or adjuvant treatment, incomplete pathological or follow-up data. BCR was defined as 2 consecutive PSA values >0.2 ng/ml after RP. CP was identified as skeletal lesions, local or loco-regional recurrence. CRD was defined as death from PCa. All men were divided into two groups according to BCR. The chi-square and t tests were used to compare baseline characteristics between groups. Biochemical progression free survival (BPFS), clinical progression free survival (CPFS) and cancer specific survival (CSS) rates were estimated using Kaplan-Meier analysis. Patients with detected BCR were analyzed for prediction of CP and CRD with respect of time until BCR. The impact of baseline parameters on BCR, CP and CRD was assessed by Cox regression analysis. BCR, CP and CRD rates were 47.8% (207/433), 11.3% (49/433) and 5.5% (24/433) respectively. Median (quartiles) time of follow-up after RP was 64 (40-110) months. 10-year BPFS rate was 34.2% CPFS - 81%, CSS - 90.1%. Men with detected BCR were analyzed for prediction of CP and CRD with respect of time until BCR. The most informative cut-off for time from RP until CP and CRD was ≤1 year (p<0.008). According to this cut-off, men were divided into 2 groups: BCR detected within 1-year and after 1-year period. 10-year CPFS was 49.8% in men with early BCR vs 81.1 % in men with late BCR, CSS was 70.9% vs 92.8% (p=0.001). Multivariable analysis confirmed that time until BCR within 1 year predicts CP (p=0.005) and CRD (p=0.03). Early BCR is associated with poorer oncological outcomes. Presented results may help both improve follow-up strategy and opt for more aggressive multimodal treatment of HRPCa men with very early BCR.